m6A-related lncRNAs are potential biomarkers for the prognosis of COAD patients - Xu, Chenyang; He, Tingting; Shao, Xinxin; Gao, Ling; Cao, Lei (Frontiers in Oncology, 2022)
Background: Colon adenocarcinoma (COAD) is the most common subtype of colon cancer. However, the 5-year survival rate of COAD patients remains unsatisfactory. N6-methyladenosine (m6A) and lncRNAs play essential roles in the occurrence and development of COAD. Herein, we are committed to establish and validate a prognostic m6A-related lncRNA signature. Methods: We obtained m6A-related lncRNAs by coexpression. The m6A-related lncRNA risk signature (m6ALncSig) was developed via univariate, LASSO and multivariate Cox regression analyses. Kaplan-Meier (KM) survival curves, gene set enrichment analysis (GSEA), as well as nomogram generation were conducted to assess m6ALncSig. In addition, the potential immunotherapeutic signatures were also discussed. Real time PCR and CCK8 analysis were performed to evaluate the expression and functions of lncRNA UBA6-AS1 which was selected. Results: The risk signature comprising 14 m6A-related lncRNAs (m6ALncSig) was established, which possessed a superior predictive ability of prognosis. Meanwhile, m6ALncSig was linked to immune cell infiltration. The level of UBA6-AS1 expression was validated in seventeen pairs of COAD samples. In cell function experiments, UBA6-AS1 knockdown attenuated cell proliferation capacity. Conclusions: Collectively, m6ALncSig could serve as an independent predictive factor for COAD and accurately estimate the outcome for COAD patients. Importantly, UBA6-AS1 was first identified as an oncogene in COAD.